Efficacy and safety of ECG‐synchronized pulsatile extracorporeal membrane oxygenation in the clinical setting: The SynCor Trial. Issue 3 (26th December 2021) - Voigt, Ingo; Spangenberg, Tobias; Ibrahim, Tareq; Bradaric, Christian; Viertel, Achim; Tallone, Ezequiel Marcelo; Skurk, Carsten; Abel, Peter; Graf, Jochen; Rinne, Torsten; Böhm, Jürgen; Ghanem, Alexander; et al.
Abstract: Introduction: Mechanical circulatory support (MCS) devices are increasingly used as a treatment option in resuscitation or in patients with cardiogenic shock (CS). Prophylactic implantation in high‐risk percutaneous coronary interventions (HRPCI) is another upcoming indication. The i‐cor ECG‐synchronized cardiac assist device combines the hemodynamic support of a veno‐arterial extracorporeal membrane oxygenation (VA‐ECMO) with the ability to generate a pulsatile flow and thus decreasing adverse effects of VA‐ECMO on myocardial function. Aim of this study was to obtain data concerning feasibility, safety and outcomes in both indications. Methods: A total of 47 patients (34 HRPCI, 13 CS) were included in nine German centers and participated in this study. Demographic and clinical parameters, procedural as well as follow‐up data were prospectively recorded and analyzed. Results: Device implantation and initiation of ECG‐synchronized cardiac assist was technical successful in all cases and no failures of the consoles or disposable parts were observed. Furthermore, intended percutaneous coronary interventions and successful weaning from cardiac assist was achieved in 97.1% of HRPCI patients. We observed a 30d‐survival of 94.1% in the HRPCI group and 69.2% in the CS group. Main complications in both groups were bleeding events (14.7% HRPCI, 23.1% CS) and critical limb ischemia (2.9% HRPCI, 38.5% CS). Conclusion: The i‐cor ECG‐synchronized cardiac assist device appears safe and feasible showing clinical outcomes comparable to existing data in the setting of high‐risk percutaneous coronary interventions and acute cardiogenic shock. Further prospective trials are warranted to identify optimal patient and interventional characteristics that will benefit most of this novel kind of mechanical circulatory support. Abstract : ECG‐synchronized cardiac assist combines the potent hemodynamic support with the ability of decreasing well described adverse effects on myocardial function of veno‐arterial extracorporeal membrane oxygenation. Forty seven patients [34 high‐risk percutaneous coronary interventions (HRPCI), 13 cardiogenic shock (CS)] were included to obtain data concerning feasibility, safety and outcomes in both indications. The i‐cor ECG‐synchronized cardiac assist device appears safe and feasible. It is associated with short‐term clinical outcomes comparable to existing literature in the setting of HRPCI and acute CS.